Localized Global Economies on the Northern Borderlands of Mexico and Morocco - Trinidad Requena, Antonio; Soriano-Miras, Rosa M.; Solís, Marlene; Kopinak, Kathryn; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This comparative study examines the processes of development and the configurations of export industries in northern Morocco and on the northern border of Mexico. As the contributors explore the similar characteristics of these two borders, they also examine how the global economy circulates around "places of production"-sites advantageous to the development of export industries. Focusing on transnational firms and the working conditions, settlement processes, and migratory flows they engender, this volume considers if a convergence toward a global culture is inevitable in places of production, or if local resistance emerges in response to the impact of the global.
1. Introduction: Global Localized Economies in a Comparative Perspective; Antonio Trinidad Requena, Rosa M. Soriano-Miras and Marlene Solís -- 2. Globalization as teh Worldwide Context for Understanding Local Dynamics; Antonio Trinidad Requena, Francisco Entrena Durán, and Marlene Solís -- 3. Multi-Site Comparative Studies and Mixed Research Designs in the Study of the Glocal; Rosa M. Soriano-Miras, Antonio Trinidad Requena and Kathryn Kopinak -- 4. Transnational Firms as an Example of Industrial Relocation: Tijuana (Mexico) and Tangier-Tétouan (Morocco); Antonio Trinidad Requena, Marlene Solís, and José Manuel García Moreno -- 5. Working Conditions in Border Export Industries and Migration; Kathryn Kopinak, Cirila Quintero Ramírez, and Jenna Hennebry -- 6. Settlement Process and Habitable Space; Marlene Solís, Inam Benali, and Rodolfo Cruz -- 7. Moving to Stay or Staying to Move? Borderlands and Internal Migrants Negotiating Work and Mobility in Export Processing Areas of Tijuana and Tangier-Tétouan; Jenna Hennebry, Francisco Barros-Rodriguez, and Kathryn Kopinak -- 8. A Synthesis: The Relationship between the Global and the Local in Industrial Relocation on the Northern Borders of Mexico and Morocco; Rosa M. Soriano Miras.
Keywords: Economic sociology; Industrial sociology; Sociology, Urban; Social structure; Equality; Political sociology; Emigration and immigration; Economic Sociology; Sociology of Work; Urban Sociology; Social Structure; Political Sociology; Human Migration